Benefits of Inggir-Inggir Fruit (Solanum Sanitwongsei Craib.) for Reducing Hypertension Pressure - Qurrohman, Taufiq; Lubis, Ayu Ulfah Nur (International Journal of Public Health Excellence (IJPHE), 2024)
Hypertension is one of the silent killer diseases known as cardiovascular disease. Increased blood pressure and an unbalanced lifestyle can increase the risk factors for the emergence of various diseases such as coronary arteries, heart failure, stroke, and kidney failure. The purpose of this research is to determine the blood pressure lowering effect of inggir-inggir fruit ethanol extract on normotensive Wistar rats and to determine the blood pressure lowering effect of inggir-inggir fruit ethanol extract on hypertensive Wistar rats. This study uses an experimental method that is to determine the effect of the independent variable on the dependent variable with the research stages. The results of statistical analysis showed that the EEBI group doses of 50 mg / kg bw, 100 mg / kg bw and 150 mg / kg bw were not significantly different (p> 0.05) with the control group (CMC-Na 0.5%) or the positive comparison group (bisoprolol) in reducing TDS, TDD, DJ and TAR of normotensive Wistar rats. The results of statistical analysis showed that EEBI doses of 50 mg / kg bw, 100 mg / kg bw and 150 mg / kg bw can reduce TDS, TDD, and TAR of hypertensive Wistar rats significantly (p < 0.05) compared to the normal group without any administration and the CMC-Na 0.5% control group but could not reduce the DJ of hypertensive Wistar rats significantly (p> 0.05) with the normal group without any administration and the CMC-Na 0.5% group. EEBI dose of 50 mg/kg bw is the best group to reduce TDS, TDD and TAR.